Vault [compact disc] : 19 80 - 19 95 (Mercury, 1995)
The definitive hard rock band of the '80s; not many captured the spirit of the times as did Def Leppard. Fifteen of their best jams include cuts like Pour Some Sugar on Me; Photograph; and Let's Get Rocked.